(untitled) (Journal of Engineering, 2024)
A partially tied piled foundation raft where both horizontal and vertical movements will be tamed. Interfacing RSTP changes are in structural dynamics and the way the forces are distributed. Nevertheless, the overall seismic behavior of this type of foundation in medium dry sand soil links to the pile raft foundation system with partial structural connection has not been studied adequately. To fill this gap we experimentally tested ten pile and group pile layouts in the laboratory in order to explore the interaction of the cushion layer with piles at different spacing. These tests concern the displacement mechanism of the raft foundation and the stressing change of the RSTP layers that occur during earthquakes. The results showed that using RSTP layers helps to minimize the variations in displacement between patterns with connected piles and those with disconnected piles when subjected to shaking loads. The pattern 1DR6cm showed a high settlement reduction ratio compared with 1DR2cm. Pattern 2C2D appeared less reduction in the vertical displacement. More significant displacements and rotating behavior anticipate lateral shaking due to reduce the number of connected piles for pattern 1C4D compare with pattern 4C1D. The pattern 3C6DHR2cm decreased the vertical displacement by 48.4% using one layer of RSTP. Using three layers of RSTP contributes to reducing the displacement by 36.4%. The number of the piles in a connection condition with the piled raft and the cushion thickness belongings on the strain deformation values.